Ticket Payment Information System On The Sea Beach Light Using Simple Additive Weighting Method - Siswanto, Eko; Abdur rohman, Bayu (Universitas Islam Negeri Walisongo Semarang, 2019)
The Sea Beach Cahaya is one of the rising beach attractions in Kendal Regency, Central Java. In general, the tourism object of The Sea Pantai Cahaya still does not use many computer systems in their daily lives. As with tourism ticket purchases and also entrance tickets, vehicles that still use ticket paper as proof of payment, it is often disrupted if it is still fussing with the queue conditions and questions by visitors. On the other hand, report data collection is still considered slow.One way to overcome the above problems is to make a ticket payment system that is computerized using the SAW (Simple Additive Weighting) method, replace paper tickets with a card model and also use the network to shorten report generation.